An anthology of theories and models of design : philosophy, approaches and empirical explorations - Blessing, Lucienne T. M.; Chakrabarti, Amaresh (Springer London, 2014)
While investigations into both theories and models has remained a major strand of engineering design research, current literature sorely lacks a reference book that provides a comprehensive and up-to-date anthology of theories and models, and their philosophical and empirical underpinnings; An Anthology of Theories and Models of Design fills this gap. The text collects the expert views of an international authorship, covering: ·         significant theories in engineering design, including CK theory, domain theory, and the theory of technical systems; ·         current models of design, from a function behavior structure model to an integrated model; ·         important empirical research findings from studies into design; and ·         philosophical underpinnings of design itself. For educators and researchers in engineering design, An Anthology of Theories and Models of Design gives access to in-depth coverage of theoretical and empirical developments in this area; for practitioners, the book will provide exposure to theoretical and empirical foundations to methods and tools that are currently practiced as well as those in the process of development.